Using Extended-Release Injectable Aripiprazole for the Successful Treatment of Depressive Symptoms in Bipolar I Disorder - Joseph Kuo; Shih-Ku Lin (Case Reports in Psychiatry)
Extended-release injectable (ERI) aripiprazole is indicated for schizophrenia and maintenance monotherapy of bipolar I disorder. Clinical trials of aripiprazole failed to exhibit efficacy in the treatment of bipolar depression. It has been suggested that relatively high doses, rapid titration of dose, a high dropout rate, and a high placebo effect might be the reasons of its ineffectiveness. Here, we report a case of a 39-year-old woman with bipolar depression who was successfully treated with ERI aripiprazole.